PENGARUH METODE BERCERITA DENGAN MEDIA GAMBAR TERHADAP PENINGKATAN KEMAMPUAN BICARA PADA ANAK USIA 4-5 TAHUN DI TAMAN KANAK-KANAK BUDHIYASA SANGSIT: Array (Midwinerslion : Jurnal Kesehatan STIKes Buleleng, 2018)
Introduction: Storytelling Method with Picture Media is one of the speaking skill development which was able to improve several physical aspects or children psychology. Methods: The research design was pre-experimental with one group pre-post test design with 24 respondents which was chosen through non- probabilitysamplingtechnique with sample criteria. The speaking ability measurement was done by Denver II observation sheet. The purpose of this study to know there The Effect of Storytelling Method with Picture Media toward Improvement of Children Speaking Ability in 4-5 Years Old at Preschool Kumara Sentana in Pacung Village. This study used Paired t-test with significant target Î±=0,05..Results: The result data obtained with mean of pre test55,00 and the mean of post test 61,67. The test result using Paired t-testwas obtained score ppre and post(0,011) < Î± (0,05), which meantsthat H0 was rejected and Ha was accepted. Conclutions: there isby effect of storytelling method with picture media toward the improvement of children speaking ability at 4-5 years old in KindergartenBudhiyasa Sangsit.